Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1101/2021.02.16.21251850
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparison of performance metrics for cloth face masks as source control devices for simulated cough and exhalation aerosols

Abstract: Universal mask wearing is recommended by the Centers for Disease Control and Prevention to help control the spread of COVID-19. Masks reduce the expulsion of respiratory aerosols (called source control) and offer some protection to the wearer. However, masks vary greatly in their designs and construction materials, and it is not clear which are most effective. Our study tested 15 reusable cloth masks (which included face masks, neck gaiters, and bandanas), two medical masks, and two N95 filtering facepiece res… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 40 publications
(41 reference statements)
1
37
0
Order By: Relevance
“…ASTM standardized tests for filtration efficiency and inhalation airflow resistance measurements from unmodified medical and cloth face masks were performed using automated filter testers (Models 8130 and 8130A, TSI) as previously described. 10 Briefly, medical and cloth face masks were secured to a test plate using beeswax. Pleats on the unmodified medical face masks were expanded prior to measurement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ASTM standardized tests for filtration efficiency and inhalation airflow resistance measurements from unmodified medical and cloth face masks were performed using automated filter testers (Models 8130 and 8130A, TSI) as previously described. 10 Briefly, medical and cloth face masks were secured to a test plate using beeswax. Pleats on the unmodified medical face masks were expanded prior to measurement.…”
Section: Methodsmentioning
confidence: 99%
“…6, 7 Face masks provide a physical barrier to the expulsion of both aerosols and droplets, and offer limited personal respiratory protection against aerosols that may enter through the nose and mouth. 8-10…”
Section: Introductionmentioning
confidence: 99%
“…The source simulator was based on a system used to test masks as source control devices for respiratory aerosols. [19,20] The simulator uses an elastomeric bellows driven by a computer-controlled linear motor to reproduce human coughing and breathing airflows. The source simulator includes a manikin headform that has pliable skin mimicking the elastic properties of human skin in order to create a realistic simulation of how each source control device would fit a human face.…”
Section: Respiratory Aerosol Source Simulatormentioning
confidence: 99%
“…[18] Two quantitative source control studies by our group using an aerosol simulator found that cloth face masks and medical masks typically blocked 40%-60% of coughed and exhaled aerosol particles and were more effective as the particle size increased. [19,20] In a subsequent study, we found that if a medical mask was knotted and the pleats were tucked to improve the fit of the mask, the mask blocked 77% of the aerosol particles, and the aerosol blocking could be increased to 85% by wearing a cloth mask over a medical mask (double masking). [21] We examined the efficacy of universal masking by placed a respiratory aerosol simulator (simulating a "source" person coughing or exhaling respiratory aerosols) and a breathing simulator (simulating a "recipient" person inhaling the aerosols) in a small room with aerosol particle measurement instruments.…”
mentioning
confidence: 99%
“…Many factors that impact the efficiency of masks in reducing exposure to aerosols including the pressure difference across the mask, the direction of flow through a mask (inhalation versus exhalation), filter efficiency, pliability of mask material, and the fit of the mask on the user's head (Lindsley et al 2021;Pan et al 2021). The last two factors can influence the amount of leakage around the mask.…”
Section: Masksmentioning
confidence: 99%